Student's Understanding of Graph Based on Information-Processing - Mampouw, Helti Lygia; Lukito, Agung; Suwarsono, St. (International Journal of Active Learning, 2016)
This study is a preliminary research on how students understand patterns. Students' understanding of something is a cognitive phenomenon as, according to information processing perspective, an integral part of the stimulus, receiving, encoding, storing and retrieving information. This paper aims to describe the information processing by students when they interpret the graph as a task that was delivered using takjil context. There are 9 seven graders aged 11-12 years in various mathematics ability that three students in each its category high, mid and low. It was found that: (1) The graph given in the task attract students' attention with various reasons. (2) The level of abstraction and processing is in accordance with students' mathematical abilities. (3) The number of words related to the context activated at certain period was determined by reviews of their experiences with similar contexts. (4) Concepts of a new schemes were not solely determined by the students' mathematical abilities. Broadly, this study recommends students to have learning experiences through varying contexts and gain extensive experiences to develop appropriate and useful cognitive schemes for solving problems.How to CiteMampouw, H. L., Lukito, A., & Suwarsono, S. (2016). Student's Understanding of Graph Based on Information-Processing. International Journal of Active Learning, 1(1).